Prevalence of multidrug resistance tuberculosis in adult patients in India: A systematic review and meta-analysis - Charan, Jaykaran (J Family Med Prim Care, 2019)
BACKGROUND: Multidrug resistance tuberculosis (MDR-TB) is an important public health problem for India but there is a paucity of data related to the prevalence of MDR-TB in India. This systematic review and meta-analysis was designed to synthesize evidence regarding the prevalence of MDR-TB in adult patients in India. METHODS: PubMed and Google Scholar were searched to find different observational studies reporting MDR-TB prevalence in India. Data related to MDR-TB prevalence were pooled for the analysis. PubMed was searched by using different MeSH words. Prevalence was reported with 95% confidence interval (CI). A separate analysis was done for new cases and previously treated cases. Random effect model was used and heterogeneity was assessed by I(2) and Cochran Q test. RESULTS: MDR-TB prevalence in new cases were 3% (95% CI 2%-5%, I(2) = 95.3%). There was difference in prevalence between different methods of measurement of MDR-TB and study designs. MDR-TB prevalence in previously treated cases was found to be 35% (95% CI 29%-41%, I(2) = 98.7%). Results vary with the method of measurement as well as the study design. CONCLUSION: MDR-TB prevalence in previously treated patients was found higher compared to the reported values in national surveys. There is a need for large scale cross-sectional study to verify the findings observed in this review.